Swedish-Finnish dictionary: Office material - Language Council of Sweden, Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Swedish-Swedish/Finnish glossary containing list of office material words. Published in Kieliviesti 1/2005. Contains approximately 150 entries. 2005.

Svensk-sverigefinsk ordlista med kontorsmaterielord. Publicerades i Kieliviesti 1/2005. Innehåller ca 150 ord. 2005.
Svensk-finsk ordlista: kontorsmateriel
Keywords: office workers; kontorsarbetare; Office Management; Kontorsorganisation; word list; ordlista; Language and linguistics; Språk och lingvistik; SOCIETY AND CULTURE; SAMHÄLLE OCH KULTUR; Languages and Literature; Språk och litteratur; Comparative Language Studies and Linguistics; Jämförande språkvetenskap och allmän lingvistik